Polysaccharide-protein complex-decorated selenium nanosystem as an efficient bone-formation therapeutic. Issue 32 (25th July 2018) - Yu, Siming; Luk, Kar-Him; Cheung, Siu-To; Kwok, Kevin Wing-Hin; Wong, Ka-Hing; Chen, Tianfeng
Abstract : PTR-SeNPs with high stability were fabricated, which demonstrated excellent in vitro and in vivo osteogenic effects via BMP-2/Smad-mediated signaling pathways. Abstract : Polysaccharide-protein complex-coated selenium nanoparticles (PTR-SeNPs) system has been rationally designed and identified as a potent bone-formation therapeutic to antagonize osteoporosis. The nanosystem presents high cellular uptake in osteoblast cells and significantly enhances bone formation in vitro and in vivo, mainly through BMP-2/Smad-mediated signalling pathways.